Improving the Students’ Participation In Speaking by Using Drilling Technique: A Classroom Action Research in the X Grade of SMK Ma’arif 1 Kebumen in the Academic Year 2019/2020 - Mitsalin, Endah; Catur Pamungkas, Apri (English Education and Literature Journal (E-Jou), 2021)
The aims of this research were to describe how the students’ participation in speaking learning process by using drilling technique and to improve the students’ speaking ability in the speaking learning process through drilling technique. This research was conducted by using Classroom Action Research (CAR). The population of this research is the X grade of MM A SMK Ma’arif 1 Kebumen in the academic year 2019/2020 which is consisted of 36 students. This research was conducted in two cycles which each cycle consists of planning, acting, observing, and reflecting. The research finding showed in qualitative and quantitative data. In qualitative data showed that before treatment, the contributions of the students were low, but after treatment most of them were contributed to the lesson. They also did not want to be voluntary when the teacher asked questions but, after treatment they became active to answer the questions and participated actively with the lesson. In quantitative data showed that the mean points of their participation point was 33, in pre-test was 41,6, from post-test 1 was 60,5 and in the post-test 2 was 78,9. It can be concluded that from the data of observation, pre-test, post-test 1, and post-test 2 the points of students’ participation were improved. Moreover, based on the table of speaking score, in pre-test the mean points of their speaking score was 58,6, from post-test 1 the mean points of their speaking score was 72,9 and in the post-test 2 the mean points of their speaking score was 80,1. It can be concluded that drilling technique could improve the students’ participation in speaking at the X grade of MM A SMK Ma’arif 1 Kebumen. Therefore, it is recommended that: (1) it is better for teachers to apply this method in the teaching speaking; and (2) future researchers can conduct research in another topic discussion and different English language skill. Keyword: Participation, Speaking, Drilling Technique Tujuan dari penelitian ini adalah untuk menggambarkan bagaimana partisipasi berbicara siswa dalam proses pembelajaran dengan menggunakan drilling teknik dan untuk meningkatkan kemampuan berbicara siswa dalam proses pembelajaran melalui drilling teknik. Penelitian ini dilakukan dengan menggunakan Penelitian Tindakan Kelas (PTK). Populasi penelitian ini adalah kelas X MM A SMK Ma'arif 1 Kebumen pada tahun akademik 2019/2020 yang terdiri dari 36 siswa. Penelitian ini dilakukan dalam dua siklus dimana setiap siklus terdiri dari perencanaan, tindakan, pengamatan, dan refleksi. Temuan penelitian menunjukkan dalam data kualitatif dan kuantitatif. Dalam data kualitatif menunjukkan bahwa sebelum adanya tindakan kelas, kontribusi siswa rendah, tetapi setelah adanya tindakan kelas sebagian besar dari mereka berkontribusi pada pelajaran. Mereka juga tidak mau dengan sukarela menjawab ketika guru mengajukan pertanyaan tetapi, setelah adanya tindakan kelas mereka menjadi aktif untuk menjawab pertanyaan dan berpartisipasi aktif dengan pelajaran. Dalam data kuantitatif menunjukkan bahwa rata-rata dari poin partisipasi mereka adalah 33, pada pre-test adalah 41,6, dari post-test 1 adalah 60,5 dan pada post-test 2 adalah 78,9. Selain itu, berdasarkan nilai berbicara, pada pre-test poin rata-rata skor berbicara mereka adalah 58,6, dari post-test 1 poin rata-rata skor berbicara mereka adalah 72,9 dan pada post-test 2 poin rata-rata dari skor berbicara mereka adalah 80,1. Dari hasil data diatas, dapat disimpulkan bahwa drilling teknik dapat meningkatkan partisipasi siswa dalam berbicara di kelas X MM A SMK Ma'arif 1 Kebumen. Oleh karena itu, direkomendasikan bahwa: (1) lebih baik bagi guru untuk menerapkan metode ini dalam pengajaran berbicara; dan (2) peneliti lain nantinya dapat melakukan penelitian dengan topik lain dan keterampilan bahasa Inggris yang berbeda. Kata kunci: Partisipasi, Berbicara, Drilling Teknik